2010
DOI: 10.5152/tjr.2010.06
|View full text |Cite
|
Sign up to set email alerts
|

Associated Factors with Pain and Disability in Patients With Knee Osteoarthritis

Abstract: ÖzetAmaç: Diz osteoartriti (OA) olan hastalarda ağrı ve fonksiyonel düzeyle ilişkili etkenleri belirlemektir. Yöntem ve Gereçler: Diz OA tanısı alan 161 hasta çalışmaya alın-dı. Hastaların yaş ortalaması 62.4± 8.7 yıl olup ortalama semptom süresi 43.76± 26.6 aydı. Hastaların yaş, cinsiyet, vücut kütle indeksi, eğitim düzeyi, sigara ve düzenli egzersiz alışkanlığı ve semptom süreleri kaydedildi. Ön-arka ve lateral diz grafilerinde Kellgren-Lawrence skorları hesaplandı. Hastaların fonksiyonel düzeyi Western Onta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
0
15
0
4
Order By: Relevance
“…Pain and functional limitation are the main manifestations of patients with knee OA, and pain is the main cause of functional impairment; pain-related functional impairment may further aggravate the severity of knee OA [35,39].Knee OA is a degenerative disease that increases with age [40]. In this study, however, we found that age and course of disease had little effect on knee osteoarthritis severity.…”
Section: Discussionmentioning
confidence: 59%
“…Pain and functional limitation are the main manifestations of patients with knee OA, and pain is the main cause of functional impairment; pain-related functional impairment may further aggravate the severity of knee OA [35,39].Knee OA is a degenerative disease that increases with age [40]. In this study, however, we found that age and course of disease had little effect on knee osteoarthritis severity.…”
Section: Discussionmentioning
confidence: 59%
“…Few other authors also found similar results in their studies. 11,12 Our results have shown that the disability is positively associated with pain and stiffness in knee joint rather than X-ray findings. Similar results were illustrated in the studies conducted by McAlindon et al 13 and Jordan et al 14 that knee pain brings about more disability then the severity of osteoarthritis on knee radiographs.…”
Section: Discussionmentioning
confidence: 62%
“…We included 21 studies published in English, and the characteristics of the included studies were shown in Table 1 [ [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] ]. These 21 studies reported a total of 1315 participants aged 40–72 years.…”
Section: Resultsmentioning
confidence: 99%